Marine toxins and nephrotoxicity:Mechanism of injury - Sitprija, Visith; Sitprija, Siravit (Toxicon (Oxford), 2019)
Marine toxins are known among several causes of toxin induced renal injury. Enzymatic mechanism by phospholipase A2 is responsible for acute kidney injury (AKI) in sea snake envenoming without any change in cardiac output and systemic vascular resistance. Cnidarian toxins form pores in the cell membrane with Ca influx storm resulting in cell death. Among plankton toxins domoic acid, palytoxin and maitotoxin cause renal injury by ion transport into the cell through ion channels resulting in renal cell swelling and lysis. Okadaic acid, calyculin A, microcystin LR and nodularin cause AKI by serine threonine phosphatase inhibition and hyperphosphorylation with increased activity of Ca2+/calmodulin – dependent protein kinase II, increased cytosolic Ca2+, reactive oxygen species, caspase and P53. Renal injury by plankons is mostly subclinical and requires sensitive biomarker for diagnosis. In this respect repeated consumption of plankton toxin contaminated seafood is a risk of developing chronic renal disease. The subject deserves more clinical study and scientific attention. •Renal injury by marine toxins of sea snakes, cnidarians and planktons and the mechanisms are discussed.•Some plankton toxins can cause renal injury.•Renal injury associated with plankton toxin contaminated seafood can be subclinical.•Frequent contaminated seafood consumption may possibly lead to chronic renal disease in the long run.•Looking toward future with global changes awareness, attention and clinical study with sensitive urinary biomarkers are required in this area.